Factors contributing to online game addiction in adolescents: a systematic review - Nursalam, Nursalam; Iswanti, Dwi Indah; Agustiningsih, Nia; Rohmi, Faizatur; Permana, Bhakti; Erwansyah, Rio Ady (Intelektual Pustaka Media Utama, 2023)
The excessive use of online games can disturb the psychological, physiological, and behavioral balance of adolescents. This study aimed to identify the factors contributing to online game addiction. On databases like Scopus (20 articles), ProQuest (113 articles), SAGE (214 articles), and Springer (596 articles), published within the last five years, a systematic review was carried out using the population, intervention, comparison, outcome, study design (PICOS) framework. The articles that were chosen employed empirical quantitative, qualitative, or mixed-methods research on young people who were addicted to online games and were published between 2018 and 2023. The review's inclusion criteria were met by 25 papers. Factors can increase the risk of adolescents experiencing online game addiction, including adolescent factors consisting of, adolescent life satisfaction, and duration of smartphone use, parenting and communication, parental support, and parental income, friendship relationships and the school environment. These findings are expected to serve as the foundation for parents and teenagers to identify the cause of problems in order to reduce harmful consequences. Nurses are expected to be able to identify elements that contribute to adolescent online game addiction and devise interventions to assist adolescents in liberating themselves.